Kultura organizacyjna - metodologia badań - Stańczyk, Sylwia (Organizational Culture - Research Methodology, 2008)
This article indicates the main methodological problems of national and multinational organizational culture’s research. These problems are very important in the face of an unforeseeable character of organizational culture, very complex and complicated structure and in the face of many different science views of this conception. The considerated problems and conclusions in this paper are based on literature studies, literature studies results of an empirical research, and the author’s own research work.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 214-222